Held to ransom: Parents of self-harming adults describe their lived experience of professional care and caregivers - Lindgren, Britt-Marie (CoAction Publishing, 2010)
The aim of the study was to discover and describe lived experiences of professional care and caregivers among parents of adults who self-harm. Narrative interviews were conducted with six parents of daughters with self-harming behaviours and analysed using a phenomenological hermeneutic approach. The meanings of the parents' narratives of their lived experiences of professional care and caregivers were interpreted as their being involved in ‘limit situations’ comparable to hostage dramas. Several meaningful themes contributed to this interpretation: being trapped in a situation with no escape; being in the prisoner's dock; groping in the dark; and finding glimmers of hope. Parents of daughters who were in care because of self-harming often felt obliged to pay an emotional ransom, which included feelings of being accused, being ‘broken’, being confused, and feeling lost. Moments of peace occurred as welcome breaks offering a short time of rest for the parents. Situations that were understood by the parents and solved in a peaceful way were experienced as a respite and inspired parents with hope for their daughters' recovery.